EXAMINING THE RELATIONSHIP BETWEEN CASH FLOW STATEMENT PATTERNS AND THE DIVIDEND POLICY: CASE OF LISTED ENTERPRISES IN VIETNAMESE STOCK EXCHANGE - Tran Thi Nga; Pham Quang Tin; Ngo So Phe (International Journal of Accounting, Finance and Business, 2020)
Dividend is one of the most concerned issues of shareholders because it is a reward for their investment. Dividend policy is at managers’ discretion and there is no clear explanation for this. Based on the data of Vietnamese listed firms on Hochiminh Stock Exchange from the year 2012 to 2017, this study proves the relationship between cash flow statement patterns and the dividend policy for the first time, as well as the relationship between cash flow from operating activities and dividend policies. In addition to this, the difference in the apportionment of cash flow statement patterns and dividend policy in relation to industry sectors are also confirmed in this research. The research result is useful in both theoretical and practical aspects.